Trust and the cultivation of relation-specific skills. Evidence from a multinational automotive supplier in Japan and Germany. Issue 8 (20th August 2014) - Saeki, Yasuo; Horak, Sven
Abstract : Purpose: This study draws on Asanuma's concept of relation-specific skills in order to analyse collaboration between automaker and supplier. The cultivation of relation-specific skills has been widely regarded a key factor of competitiveness in the Japanese automotive industry. Yet, the concept has been described mostly in economic terms only. This research attempts to extend this view by analysing the role of informal institutions (trust) in developing relation-specific skills. Design/methodology/approach: By drawing on expert interview data, evaluated by using content analysis, within the frame of a case study research approach, we gathered data from the leading multinational automotive supplier Bosch in its facilities in Japan and Germany. Findings: The results show that the influence of trust plays a role in determining relation-specific skills. In conclusion, we assume that cultural homophily positively influences the cultivation of relation-specific skills and recommend future research to take this assumption into account. Practical implications: Findings imply that over the course of business transactions organizational structures hardly converge leading to higher transaction cost. Moreover, Keiretsu structures are still strong in the field of automotive electronics. Originality/value: So far the concept of relation-specific skills has been regarded a "culture-free" concept. Our results provide a first indication that cultural differences affect the cultivation of relation-specific skill, and thus need to be considered integral to the concept.